THE DEADLINE FOR DEPARTURE PREVENTION FROM AN IMMIGRATION LAW PERSPECTIVE - Mulya, Ratna Pristiana; Suparno, Suparno (Ridwan Institute, 2024)
This study aims to highlight the critical need to update the provisions on departure prevention in Indonesia's Immigration Law, specifically addressing the legal uncertainty arising from the phrase